Molecular Characterization and Antimicrobial Resistance Profiling of Food Borne Pathogens from Chicken Meat in Tamil Nadu, India - Vasanthi. B; Parthiban. M; Ghadevaru Sarathchandra; Narendra Babu, R; Brindha, K (The Indian Veterinary Journal, 2023)
Antibiotic resistance is a growing concern in the poultry industry, where the misuse of antibiotics can lead to the emergence and spread of resistant bacteria. This study focused on assessing the antibiotic susceptibility of Escherichia coli and Klebsiella isolated from chicken meat swab samples (n=30) collected from local markets in and around Chennai, Tamil Nadu, India. Molecular characterization was carried out using gene-specific primers (uspA for E. coli and bla SHV for Klebsiella) and the presence of E.coli and Klebsiella isolates were confirmed in the meat samples. The Kirby-Bauer disc diffusion method was done to evaluate the susceptibility of the isolates to commercially available antibiotics. Zones of inhibition were measured following CLSI standards and classified the isolates as susceptible, intermediate, or resistant. The results revealed antibiotic susceptibility profile of E. coli and Klebsiella in chicken meat samples with the prevalence of 67%, and 33% respectively, highlighting the importance of prudent antibiotic use and food safety measures in addressing antibiotic resistance in the poultry industry.